Perencanaan Pajak Penghasilan (Tax Planning) Dalam Upaya Penghematan Pajak Pada Pt. Golden Rooster Indonesia - Rasidin, Rinaldi; Sulaiman, Sulaiman (PT. Alahyan Publisher Sukabumi, 2023)
There is a tax saving strategy legalized by the Tax Law, which is allowed as long as it does not violate the rules stipulated by the Tax Law and does not harm the state for this tax savings. This tax-saving effort is popular in the tax world called Tax Planning (Tax Planning). This study aims to analyze the use of tax planning and analysis of tax planning maximization. This type of research is descriptive research to conduct this research and internal data collection for the purpose of this research. The results of the study conclude that the company has not implemented tax planning optimally for the overall income tax which has an impact on corporate tax being high which should be maximized so that corporate tax is reduced. The policy in using the gross-up method or the Nett method for income tax as outlined in the contract agreement with partners, then the company policy in providing benefits to employees, so that when it is charged as an expense it is recognized as a deductible expense.